Gabriele Stein. Developing Your English Vocabulary: A Systematic New Approach - Abecassis, Michaël (Lexikos, 2005)
Gabriele Stein is professor of English linguistics at the University of Heidelberg in Germany and has published widely on lexicography and lexicology. The objective of this book is twofold: to compile a lexical core and to maximise the skills of language students by developing ways of expanding this core. It is intended to function as a teaching aid for teachers of English as well as a self-study book for learners of English as a second language. Lexical knowledge is a crucial part of language acquisition and depends on different external factors such as the age and profession of the learner, his/her goals, expectations and needs in learning a language. Beck et al. (2002) have demonstrated the small extent of the emphasis on the acquisition vocabulary in school curricula.